THE CIRCLE READING LEARNING MODEL WITH WORD CARDS TO UNDERSTANDING READ STUDENT ON EYE LESSON INDONESIAN LANGUAGE IN CLASS III OF ELEMENTARY SCHOOL - Nada Syiva Salsabila; Nurdiana Siregar (RADJA PUBLIKA, 2026)
This study aims to determine the effect of the Circle Reading learning model with word cards media on students' reading comprehension in Indonesian language subjects in grade III of elementary school. The study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design . The research sample consisted of 40 students divided into an experimental class and a control class, each consisting of 20 students. Data collection techniques were carried out through reading comprehension tests in the form of pre-tests and post-tests . Data were analyzed using descriptive and inferential statistics through normality tests, homogeneity tests, and Independent Samples T-Tests . The results showed that the average pre-test score of the experimental class was 62.75 and the control class was 62.10 with a significance value of p = 0.600 (> 0.05), so that both groups had equal initial abilities. After the treatment was given, the average post-test score of the experimental class increased to 84.55, while the control class was 71.15. The results of the Independent Samples T-Test showed a t value = 9.567 with a significance value of p = 0.600 (> 0.05). p < 0.001, Which means there is influence significant model learning Circle Reading with word cards as a medium on students' reading comprehension. Cohen's d value of 3.025 indicates size effect Which very big. With thus, model learning CircleReading with word cards is effectively used to improve students' reading comprehension in Indonesian language subjects in grade III of elementary school.